E‐Leadership in higher education: The fifth "age" of educational technology research. (17th October 2013) - Jameson, Jill
Abstract A discussion of the relative lack of research into e‐leadership in educational technology in education is followed by an outline of selected prior literature in the field. The paper proposes that, as part of a natural evolution of educational technology research, considerably more attention needs to be focused on research and development in e‐leadership. Building on selected prior literature, an updated framework of principles for effective "e‐leadership" of educational technology is proposed, with specific reference to higher education, building on selected insights derived from e‐leadership literature and on the author's experience of 30 years of professional practice, scholarship and research into educational technologies and leadership in education. The paper proposes the development of a new fifth "age" of educational technology research in which it is argued that more critical, selective, strategic e‐leadership approaches to the adoption and use of educational technology need to be progressed through research, development and training as the field matures.